Correction: Metal-organic-framework derived Co-Pd bond is preferred over Fe-Pd for reductive upgrading of furfural to tetrahydrofurfuryl alcohol - Pendem, Saikiran; Bolla, Srinivasa Rao; Morgan, David J; Shinde, Digambar B; Lai, Zhiping; Nakka, Lingaiah; Mondal, John (Dalton transactions : an international journal of inorganic chemistry, 2022)
Correction for 'Metal-organic-framework derived Co-Pd bond is preferred over Fe-Pd for reductive upgrading of furfural to tetrahydrofurfuryl alcohol' by Saikiran Pendem et al. , Dalton Trans. , 2019, 48 , 8791-8802, https://doi.org/10.1039/C9DT01190K .